Using Different-Level of Leucaena leucocephala Leaves in Concentrated Feeds to Increase Goat Farming Production - Eko Marhaeniyanto; Sri Susanti; Asmah Hidayati (Jurnal Ilmu-Ilmu Peternakan, 2023)
The potential of Leucaena leucocephala leaves as a protein supplement needs to be optimized. This research aims to evaluate the use of 10 to 40% Leucaena leucocephala leaves with 15% of crude protein to increase the production of goat farming. A total of 16 male Etawa (Jamnapari) goats with an average weight of 28.20±3.79 kg. The researchers analyzed the data using the Randomized Group Design with four treatments and four groups based on the subject's body weight. Each goat obtained basal feeds ad libitum and the concentrated feeds with 15% crude protein corresponding to each treatment Leucaena leucocephala-based concentrate (named KL, consisting of KL10%, KL20%, KL30%, and KL40%), reaching 1% of Body Weight. The supplementation of Leucaena leucocephala leaves showed an insignificant response (P>0.05) over feed consumption, digestibility, and digested feed consumption yet significantly (P<0.05) affecting the increase of body weight and feed conversion. The ADG (Average Daily Gain) of all treatments are KL10% = 84.00±27.95 g/head/day; KL20% = 99.29±40.02 g/head/day; KL30% = 67.00±45.51 g/head/day; KL40% = 88.50±23.62 g/head/day. In conclusion, the supplementation of 20% Leucaena leucocephala leaves in the concentrate of 15% crude protein results in an ADG increase reaching 99.29±40.02 g/head/day.